Death-associated kinase-related (Drak) localization in Drosophila during early embryogenesis - Siipilehto, Panu (2023)
Cells can regulate cellular processes by sensing mechanical forces in a process known as mechanotransduction. This can be achieved with cytoskeletal proteins such as actin crosslinking protein filamin. Fruit fly filamin is known as Cheerio (Cher). In this study, I focused on actomyosin regulations during the cellularization phase of Drosophila early embryogenesis. Specifically, I studied filamin, myosin regulatory light chain protein called Spaghetti squash (Sqh), and Death-associated kinase-related (Drak). Prior research has shown that filamin and Sqh colocalize during cellularization. Additionally, Drak binds to filamin, and both Drak and filamin are involved in the regulation of cellularization. Drak also phosphorylates Sqh, but its localization during Drosophila cellularization is unknown. I used Drosophila melanogaster lines that expressed Green fluorescent protein (GFP) or mCherry red fluorescent protein fusions of Cher, Drak, and Sqh. Early embryos were time-lapse imaged with confocal microscopy and analyzed with ImageJ software. Pearson’s Correlation Coefficient (PCC) was calculated for selected region-of-interests. The main results showed that a proportion of Drak localizes to actin front together with Cher. Cher and Sqh PCC increased as cellularization progresses. In contrast, Drak and Cher colocalization remained similar throughout. Drak also localized near cellular cortex between nuclear divisions and throughout the cellularization process. My results suggest that Drak may have a role in both the cortical region and in the cellularization front. These results provide further knowledge for characterizing the mechanically regulated signaling pathways of filamin.